Investigation on the heat source profile on the finished surface in grinding based on the inverse heat transfer analysis - Wang, Dexiang; Ge, Peiqi; Sun, Shufeng; Jiang, Jingliang; Liu, Xinfu (International journal of advanced manufacturing technology, 2017)
Grinding temperature field analysis is very significant to achieve controlled stress grinding and controlled grinding of affected layer depth. Heat source profile is an important basis for the grinding temperature field analysis. The heat source on the finished surface is more convenient than the heat source on the contact surface to perform grinding temperature field analysis both analytically and numerically. At present, the heat source profile on the finished surface was modeled to be rectangular, right triangular, triangular, or other shapes. However, all the modeled heat source profiles are not universally applicable under different grinding conditions. Therefore, the heat source profile on the finished surface under different grinding conditions needs to be further investigated. In this research, the inverse heat transfer analysis was performed to investigate the heat source profile on the finished surface under different grinding conditions. The investigation showed that the heat source profile on the finished surface is nearly right triangular in conventional shallow grinding, is triangular in creep feed grinding, and is close to be parabolic in HEDG (high efficiency deep grinding). Based on the investigation, the heat source profile on the finished surface was modeled as simple shapes to accommodate different grinding conditions. It was modeled to be right triangular in conventional shallow grinding and in creep feed grinding, and was modeled to be parabolic in HEDG. Error analyses of the predicted grinding temperatures obtained from the modeled heat source profiles were performed. The results showed that the modeled right triangular heat source profile is applicable in conventional shallow grinding and in creep feed grinding. The modeled parabolic heat source profile is applicable to most of the grinding parameters employed in HEDG. The modeled heat source profiles can conveniently serve as useful tools for grinding temperature field analysis in engineering.